1988
DOI: 10.1002/food.19880320606
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of milk proteins and cereal starches to obtain co‐extrudates

Abstract: Extrusion of the cereal mixtures with 25% addition of milk proteins induced several changes in the chemical and physico-chemical properties of starch. Coefficient of expansion was close to the coefficient of natural cereal flours, but the extrudates were characterized by higher water absorption. Starch was only slightly dextrinized, but it contained more nitrogen compounds and mineral salts, and less free lipids. Solubility and swelling power of the extrudates did not change in a way characteristic for cereal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…3) indicated that maximum gelatinization occurred at the highest temperature and lowest moisture, whereas minimum gelatinization occurred at the highest moisture content and the lowest barrel temperature. Low feed moisture contents may restrict flow of material inside the extruder barrel, increasing shear rate and residence time, which might increase the degree of starch gelatinization and expansion [30][31][32]. In the present study, the changes in P and SME in both HS and LS extrudates support this observation (Figs.…”
Section: Degree Of Gelatinizationsupporting
confidence: 92%
“…3) indicated that maximum gelatinization occurred at the highest temperature and lowest moisture, whereas minimum gelatinization occurred at the highest moisture content and the lowest barrel temperature. Low feed moisture contents may restrict flow of material inside the extruder barrel, increasing shear rate and residence time, which might increase the degree of starch gelatinization and expansion [30][31][32]. In the present study, the changes in P and SME in both HS and LS extrudates support this observation (Figs.…”
Section: Degree Of Gelatinizationsupporting
confidence: 92%
“…1998) when compared with the extrusion of starch alone. Composite extrudates of milk proteins (25%) and cereal starches exhibited increased density (Smietana et al . 1988).…”
Section: Introductionmentioning
confidence: 99%
“…This trend was also observed as milk proteins were added to buckwheat, barley and maize starch extrusion formulations (Smietana et al . ). The authors attributed this effect to the formation of a protein–starch complex.…”
Section: Resultsmentioning
confidence: 97%
“…Soy protein is a leading protein used in extrusion puffing, but milk proteins such as whey protein concentrates and isolates, caseinates and milk protein concentrates and isolates have also been studied (Smietana et al . ; Barraquio and van de Voort ; Onwulata et al . ; Amaya‐Llano et al .…”
Section: Introductionmentioning
confidence: 99%